Photonic Heterodyne Pixel for Imaging Arrays at Microwave and MM-Wave Frequencies. (18th October 2012) - Criado, Á. R.; Montero-dePaz, J.; de Dios, C.; García, L. E.; Segovia, D.; Acedo, P.
Abstract : The use of photonic heterodyne receivers based on semiconductor optical amplifiers to be used in imaging arrays at several GHz frequencies is evaluated. With this objective, a3 × 3 imaging array based on such photonic pixels has been fabricated and characterized. Each of the receiving optoelectronic pixels is composed of an antipodal linear tapered slot antenna (LTSA) that sends the received RF signal directly to the electrical port of a semiconductor opticalamplifier (SOA) acting as the optoelectronic mixer. Both the local oscillator (LO) and the intermediate frequency (IF) signals are directly distributed to/from the array pixels using fiber optics, that allows for remote LO generation and IF processing to recover the image. The results shown in this work demonstrate that the performances of the optoelectronic imaging array are similar to a reference all-electronic array, revealing the possibility of using this photonic architecture in future high-density, scalable, compact imaging arrays in microwave and millimeter wave ranges.